2021
DOI: 10.1016/j.msard.2021.102909
|View full text |Cite
|
Sign up to set email alerts
|

Use of geographical information systems in multiple sclerosis research: A systematic scoping review

Abstract: Introduction: Geographical Information System (GIS) and spatial analysis have an emerging role in the understanding and management of health-related outcomes. However, there is a knowledge gap about the extent to which GIS has supported Multiple Sclerosis (MS) research. Therefore, this review aimed to explore the types of GIS applications and the complexity of their visualisation in MS research. Methods: A systematic scoping review was conducted based on York's ve-stage framework. PubMed, Scopus and Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Our scoping review showed that GIS had been used very little in dementia care (14.3%) and planning (0.8%). The later finding is even less than in similar areas such as multiple sclerosis (MS) (4%) [33] and mental health care (15%) [134]. Policy planning and resource allocation are critical for optimal care of dementia across communities [135].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our scoping review showed that GIS had been used very little in dementia care (14.3%) and planning (0.8%). The later finding is even less than in similar areas such as multiple sclerosis (MS) (4%) [33] and mental health care (15%) [134]. Policy planning and resource allocation are critical for optimal care of dementia across communities [135].…”
Section: Discussionmentioning
confidence: 99%
“…The low level of publications in other European countries is striking, given the fact that dementia is a top priority in this world region [142]. Unlike multiple sclerosis, which has the most studies in European countries [33], there is a significant gap in GIS/GPS studies in dementia research and care in these countries. We suggest doing more research in this area in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting a spatial methodology using Geographical Information System (GIS) allows defining region-based patterns and trends associated with health outcomes, risk factors, and community wellbeing [ 8 ]. GIS is a computerized framework for storing, preserving, processing and presenting geographic information [ 9 ]. A study in Italy using Bayesian hierarchical spatial models highlighted that the risk of the cancers of melanoma and lip was incredibly significant for the coastal region and for body sites like the face and neck that are typically linked to high accumulated exposures, particularly in the male gender [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-spatial data include all of the other data, such as the capacity of hospitals or individual characteristics of women undergoing CS. GIS technology could develop knowledge regarding the spatial distribution of CS cases or the spatial interaction between the women using CS and the hospitals performing CS [14,15].…”
Section: Introductionmentioning
confidence: 99%